How Computational Epitope Mapping Identifies the Interactions between Nanoparticles Derived from Papaya Mosaic Virus Capsid Proteins and Immune System - Zamani-Babgohari, Mahbobeh (Curr Genomics, 2019)
BACKGROUND: Nanoparticles derived from plant viruses possess fascinating structures, versa-tile functions and safe properties, rendering them valuable for a variety of applications. Papaya mosaic Virus-Like Particles (VLPs) are nanoparticles that contain a repetitive number of virus capsid proteins (PMV-CP) and are considered to be promising platforms for vaccine design. Previous studies have re-ported the antigenicity of PMV nanoparticles in mammalian systems. MATERIALS AND METHODS: As experiments that concern vaccine development require careful design and can be time consuming, computational experiments are of particular importance. Therefore, prior to ex-pressing PMV-CP in E. coli and producing nanoparticles, we performed an in silico analysis of the virus particles using software programs based on a series of sophisticated algorithms and modeling networks as useful tools for vaccine design. A computational study of PMV-CP in the context of the immune sys-tem reaction allowed us to clarify particle structure and other unknown features prior to their introduc-tion in vitro. RESULTS: The results illustrated that the produced nanoparticles can trigger an immune response in the absence of fusion with any foreign antigen. CONCLUSION: Based on the in silico analyses, the empty capsid protein was determined to be recognised by different B and T cells, as well as cells which carry MHC epitopes.